Use of neural networks to determine the rating of an application published in the Google Play Store - Tito Durand, Rudy Roberto (2023)
Artificial intelligence is the combination of algorithms written in the form of computer code in order to be executed on a computer to emulate behaviors similar to human intelligence. In this work, the use of neural networks will be sought, which are part of artificial intelligence and allow us to solve prediction problems. A dataset based on Google Play Store app downloads and their features will be modified and the information processed to obtain output information.